Mediasi Sebagai Penyelesaian Sengketa Cerai - Ronald Fadly Sopamena (Faculty of Law, Universitas Pattimura, 2021)
Husband and wife are obliged to love each other, respect, be loyal and provide spiritual and physical assistance to each other. However, sometimes husbands and wives who live the ark of the household often experience complicated conflicts so that divorce is considered the best solution. The purpose of this study is to analyze the peace deed No. 7/Pdt.G/2020/PN Drh. The method for this research is descriptive analytical with normative juridical research using primary, secondary and tertiary data through literature and document studies. The results showed that the divorce lawsuit was processed at the Highlands District Court of Honipopu in West Seram Regency, Maluku Province. The divorce lawsuit finally ended with an agreement between the parties to end the divorce dispute which was resolved through mediation. The peace is stated in the Deed of Peace Number 7/Pdt.G/2020/PN Drh which applies as befits an agreement and has legal consequences if it is not obeyed.